PENGARUH PERATAAN LABA BERDASAR MANIPULASI AKTIVITAS RIEL TERHADAP PERSISTENSI LABA (Analisis Terhadap Laporan Keuangan Interim) - Nining Ika Wahyuni (Universitas Jember, 2010)
By using quarterly financial statement, this research aims to provide empirical evidence of the relations between income smoothing based real activities manipulation and earning persistence. This research hypothesized that income smoothing based real activities manipulation has positive effect to the earning persistence. This study investigates three types of real activity manipulation: abnormal cash flow operation, abnormal discretionary expense, and abnormal production cost. Real earning management is measured by summing the standardized of the three proxies. The numbers of companies that serve as a sample according to the criteria is consist of 63 in research period from 2004 to 2008. From this number, samples which are included into income smoothing criteria based on Eckel Model consist of 26 firms. Data were collected with purposive sampling method. The hypothesis was tested with regression. This research failed to support the hypothesis. Further, the result shows that income smoothing via real earning manipulation negatively affect the earning persistence. Keywords: Real Earning Management, Income Smoothing, Earning Persistence.